Nacerdochroa concolor (Brull? 1839) (Coleoptera: Oedemeridae): taxonomy, ecology, life cycle and larval instars - Plata-Negrache, Paulino; Alonso-Zarazaga, Miguel A. (Zootaxa, 2006)
The taxonomy, ecology and life cycle of Nacerdochroa concolor (BrullJ, 1839) is reviewed. This species is a pest of the dragon-tree, Dracaena draco. Imago, larvae and egg are described. Holoxantha Semenov, 1894, syn. nov., is synonymised with Nacerdochroa Reitter, 1893. An updated checklist of Canarian Oedemeridae is presented.